Advances in venomics. Issue 12 (27th October 2016) - Oldrati, Vera; Arrell, Miriam; Violette, Aude; Perret, Frédéric; Sprüngli, Xavier; Wolfender, Jean-Luc; Stöcklin, Reto
Abstract : The term "venomics" was coined to describe the global study of venom and venom glands, targeting comprehensive characterization of the whole toxin profile of a venomous animal by means of proteomics, transcriptomics, genomics and bioinformatics studies. Abstract : The term "venomics" was coined to describe the global study of venom and venom glands, targeting comprehensive characterization of the whole toxin profile of a venomous animal by means of proteomics, transcriptomics, genomics and bioinformatics studies. This integrative approach is supported by the rapid evolution of protein, RNA and DNA sequencing techniques, as well as databases, knowledge-bases and biocomputing algorithms. The aim of this review is to illustrate advances in the field of venomics during the last decade, addressing each step of the procedure, from sample collection to data treatment. A special focus is made on new perspectives for a better understanding of the venomous function and for fostering the discovery of new venom-derived drug candidates.